Curators in Indonesian Corporate Bankruptcy: Duties, Independence, and Implications for Corporate Dissolution - Styabudhi, Aldinno Diaz; Borman, Syahrul; Ayuningtyas, Fitri (Jurnal Ragam Pengabdian, 2026)
This article analyzes the legal position, duties, independence, and liability of curators in Indonesian corporate bankruptcy, while clarifying their relationship with corporate dissolution. It addresses a recurring normative problem: Law Number 37 of 2004 requires a curator to be independent and free from conflicts of interest, yet it does not provide sufficiently operational indicators for evaluating that independence or for distinguishing professional risk from actionable fault. The study uses normative legal research with statutory, conceptual, and analytical approaches. Primary materials include the Bankruptcy and Suspension of Debt Payment Obligations Law and the Limited Liability Company Law, supported by recent legal scholarship on curator duties, supervision, creditor protection, going concern, and professional liability. The analysis shows that a curator is a court-appointed estate administrator whose authority covers asset preservation, claim verification, business continuation when value-enhancing, liquidation, and proportional distribution. A corporate liquidator, however, operates within the dissolution regime and should not be equated automatically with a bankruptcy curator. The article proposes objective safeguards consisting of pre-appointment disclosure, continuing conflict checks, independent valuation, transparent reporting, documented decision-making, effective supervisory review, and a fault-based liability standard balanced by functional protection for good-faith conduct.